2001
DOI: 10.2741/corfield
|View full text |Cite
|
Sign up to set email alerts
|

Mucins in the gastrointestinal tract in health and disease

Abstract: Mucins form part of the dynamic, interactive mucosal defensive system active at the mucosal surface of the gastrointestinal tract. They are carbohydrate rich glycoproteins with unique molecular structure and chemical properties. The family of mucin (MUC) genes has 13 members that can be divided into secreted and membrane-associated forms each with characteristic protein domains and tissue specific glycosylation. Biosynthetic pathways have been described for the secreted and membrane-associated mucins and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
161
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(162 citation statements)
references
References 328 publications
0
161
0
1
Order By: Relevance
“…[1][2][3][4] Mucins, the carbohydrate-rich glycoprotein building blocks of the mucus gel, determine both the thickness and the major properties of mucus. 6,7 There are 21 distinct mucin genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Mucins, the carbohydrate-rich glycoprotein building blocks of the mucus gel, determine both the thickness and the major properties of mucus. 6,7 There are 21 distinct mucin genes.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the stomach, mucus helps to reduce bacterial colonization, aids in protecting the epithelium from damage induced by ingested substances, acid, and pepsin, and contributes significantly to repair of epithelial damage. [1][2][3][4] That last effect is attributable to the contribution of mucus in the formation of a microenvironment over sites of mucosal injury, which is conducive to restoration of epithelial integrity. 4 Disruption of mucus in that circumstance leads to progression of tissue injury to deeper layers of the mucosa, with significant bleeding.…”
mentioning
confidence: 99%
“…On the other hand, MUC5AC and MUC6 are two gastric type mucins that are expressed in the surface foveolar epithelium and deep antral/pyloric glands, respectively. [17][18][19] Aberrant and bidirectional gastric differentiations of foveolar mucin (MUC5AC) and pyloric mucin (MUC6) have been reported in colonic serrated adenomas and hyperplastic polyps. 20 In that article, the authors indicated that MUC5AC-positive cells are typically located throughout the entire length of the crypts, whereas cells expressing MUC6 are present only in the basal crypts.…”
mentioning
confidence: 99%
“…The characteristics and functions of this barrier have been the object of much research as Transitional metaplasia in intestinal epithelium of rats submitted to intestinal cystoplasty and treatment with L-lysine Santos AM et al changes in barrier composition are known to be associated with severe gastrointestinal problems (inflammatory bowel disorders) 22,23 , urinary diversions with intestinal segments 24 , Barrett's esophagus and colorectal cancer 22,23 . Some changes in MUC gene expression or polymorphism have been detected in inflammatory bowel disorders, but not in malignant transformation 23 .…”
Section: ■ Discussionmentioning
confidence: 99%